ENERGY SAVING IN A BOILER USING ECONOMIZERS - Armijo C., Javier (2008)
In this work we examine the boiler-economizers system to determine the effect of warm water in the efficiency of steam generation system. Solving the equations balance of matter and energy (BME) provides that there is a saving in fuel consumption as it increases the temperature of water entering the boiler, and it is achieved by improving the efficiency of steam generator. The savings on fuel economy depends on the flow of water and is about 5%.